2021
DOI: 10.3390/ijerph18042067
|View full text |Cite
|
Sign up to set email alerts
|

Forest Bathing Always Makes Sense: Blood Pressure-Lowering and Immune System-Balancing Effects in Late Spring and Winter in Central Europe

Abstract: Various formats of forest bathing have been receiving increasing attention owing to their perspectives in health promotion and the treatment of chronic lifestyle diseases. The majority of field studies are still being conducted in the Far Eastern region, and they often make psychological assessments mainly in the green season. In our pretest–posttest field experiment, twelve healthy, working-age volunteers participated in a 2-h leisurely forest walking program, first in the green season (May) and then in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 80 publications
0
28
1
1
Order By: Relevance
“…Personal characteristics such as gender, age, psychological traits and physical health contribute to modulating the extent of beneficial effects of the forest immersion. In particular, a recent study performed in Hungary showed that walking in the forest for 2 h, with minimal guidance and aimed at maintaining a slow pace, resting, observation, breathing and touching the wood produced a significant decrease of systolic blood pressure both in late spring and winter [ 12 ]. As well, a significant stimulation of NK bright cells and activation of various immune cell subsets was observed in late spring, while a slight activating and a balancing effect regarding TIM-3, an inhibitory immune checkpoint molecule, were observed in winter, thus suggesting positive forest healing effects throughout the year [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Personal characteristics such as gender, age, psychological traits and physical health contribute to modulating the extent of beneficial effects of the forest immersion. In particular, a recent study performed in Hungary showed that walking in the forest for 2 h, with minimal guidance and aimed at maintaining a slow pace, resting, observation, breathing and touching the wood produced a significant decrease of systolic blood pressure both in late spring and winter [ 12 ]. As well, a significant stimulation of NK bright cells and activation of various immune cell subsets was observed in late spring, while a slight activating and a balancing effect regarding TIM-3, an inhibitory immune checkpoint molecule, were observed in winter, thus suggesting positive forest healing effects throughout the year [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials conducted walking, staying, and exercising sessions in the forest and examined the therapeutic effect of forests. They demonstrate that forest have effects on reducing anxiety and depression [18][19][20][21], reducing stress [8,[22][23][24], promoting physiological relaxation [25][26][27][28][29][30], improving cognitive function [31][32][33], relieving inflammation [34][35][36][37], improving immune function [37][38][39][40][41], and preventing cardiovasculars [35,36,42,43]. Overall, these studies demonstrate that individuals gain health benefits through mental and physical interactions with forest elements.…”
Section: Introductionmentioning
confidence: 96%
“…People can boost sensory awareness and balance their lives by taking soothing and meditative walks in nature. Nature walks are based on a Japanese technique known as "shinrin-yoku", which translates to "forest bathing" and is sometimes referred to as "forest therapy" [3]. This technique was first developed in the early 1980s by Tomohide Akiyama, director of the Japanese Forestry Agency [4], based on the idea that cultivating a love relationship with nature can help preventative healthcare, well-being, and healing.…”
Section: Introductionmentioning
confidence: 99%